Influência dos fatores organizacionais no sucesso de projetos no setor automotivo - Santos, Izabela Andressa Machado dos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research aims to identify and to evaluate the organizational factors influencing project success in automotive companies to contribute to project management area. Project success relates to the ability to achieve the objectives proposed. Organizational factors are critical to an organization and they are considered crucial to organizational success as well as company's project success. The effectiveness of a company depends in part on its project sucess. And an important factor regarding to project is to determine the success factores because they allow evaluation and correction during the execution phase as well as learning for future projects. The questionnaire developed for this survey was sent to 401 Brazilian automotive companies which are members of SINDPEÇAD and also to the participants of the Gerenciamento de Projetos Automotivos (Automotive Project Management) group on Linkedin. We obtained 72 responses which were used in this study. Quantitative methods were used to ansewer the research questions. First, we used confirmatory factor analysis to identify the organizational factors that influence project success. The results of this analysis indicated that top management support, good communication, effective change management, organizational culture and training have a positive influence to the project success. Then we applied a multiple linear regression and we found a model that best fits the data. According to the results of this analysis, the organizational factor that has the highest rate influences to the success is the organizational culture, followed by top management support and by effective change management. From an organizational point of view, this study allows managers to analyze and understand the organizational factors present and their influences on project success, enabling better priorization and monitoring of projects, not limited only to technical issues. Based on the results, we noticed that most of...

O objetivo deste trabalho é identificar e avaliar a influência dos fatores organizacionais no sucesso doe projetos em geral, de empresas do setor automotivo, com intuito de contribuir para a área de gestão de projetos. Os fatores organizacionais são de suma importância para uma organização, sendo considerados determinantes para o sucesso organizacional, assim como o sucesso dos projetos de uma empresa. A eficácia de uma empresa depende em parte do sucesso de seus projetos. E um fator importante em relação a um projeto é a determinação dos fatores de sucesso, pois permite sua avaliação e a correção durante a fase de execução e também o aprendizado para projetos futuros. Para esta pesquisa foi desenvolvido um questionário e enviado a 401 empresas do setor automotivo brasileiro que fazem parte do SINDPEÇAS e também aos participantes do grupo Gerenciamento de Projetos Automotivos no Linkedin. Obteve-se 72 respostas, as quais foram utilizadas neste estudo. Para responder as questões de pesquisa foram utilizados métodos quantitativos. Primeiramente, utilizou-se a análise fatorial confirmatória para verificar e identificar os fatores organizacionais que influenciaram no sucesso de projetos, os resultados desta análise indicaram que o apoio da alta administração, a boa comunicação, a gestão de mudanças eficaz, a cultura organizacional e o treinamento influenciam positivamente no sucesso de projetos. Em seguida foi realizada a análise de regressão linear múltipla encontrando-se um modelo que melhor se ajusta aos dados. Nos resultados desta análise, o fator organizacional que apresenta a maior taxa de influencia no sucesso é a cultura organizacional, seguido pelo apoio da alta administração e pela gestão de mudanças eficaz. Do ponto de vista organizacional, seguido pelo apoio da alta administração e pela gestão de mudança eficaz. Do ponto de vista organizacional, este estudo permite aos gestores analisarem...
Keywords: Administração de projetos; Empresas; Sucesso nos negocios; Project management